Synthesis and characterisation of highly branched polyisoprene: exploiting the "Strathclyde route" in anionic polymerisation. Issue 21 (26th March 2018) - Habibu, Shehu; Sarih, Norazilawati Muhamad; Mainal, Azizah
Abstract : Copolymerisation of isoprene and divinylbenzene was achieved in toluene via anionic chain transfer polymerization to yield highly branched polymers with good solution and rheological properties. Abstract : This work aimed at developing a synthetic route towards highly branched poly(isoprene) from commercially available raw materials, in good yield and devoid of microgelation, i.e., to prepare a completely soluble polymer via the versatile technique anionic polymerisation. The polymerisations were conducted under high vacuum conditions using sec -butyllithium as initiator at 50 °C in toluene. Toluene served both as a solvent and as a chain-transfer agent. The polar modifier used was tetramethylethylenediamine (TMEDA), and a commercial mixture of divinylbenzene (DVB) was employed as the branching agent for the "living" poly(isoprenyl)lithium anions. The nature of the reaction was studied on the TMEDA/Li ratio as well as the DVB/Li ratio. The obtained branched polymers were characterised by triple detection size exclusion chromatography (SEC), proton nuclear magnetic resonance spectroscopy ( 1 H NMR), differential scanning calorimetry (DSC) and melt rheology. Broad molecular weight distributions have been obtained for the highly branched polymer products. 1 H NMR spectroscopy reveals the dominance of 3, 4-polyisoprene microstructure. It was found that the complex viscosities and dynamic moduli of the branched samples were much lower compared to their linear counterparts. The results conform with earlier findings by the "Strathclyde team" for radical polymerisation systems. This methodology has the potential of providing soluble branched vinyl polymers at low cost using the readily available raw materials.